AUTONOMOUS AIR PURIFIER USING IOT WITH CLOUD-BASED MONITORING - Md Ifran; Md Rahman Shareef; Md Malik Eliyas; Md Inayathullaha (International Educational Journal of Science and Engineering, 2026)
Air pollution has emerged as a major environmental and health concern due to rapid industrialization and urban expansion. Indoor air contamination, in particular, can lead to respiratory disorders, allergies, and reduced quality of life. This paper presents the design and implementation of an autonomous air purification system integrated with Internet of Things (IoT) technology and cloud-based monitoring. The system employs gas sensors to continuously detect pollutants such as carbon dioxide, smoke, and harmful gases. A NodeMCU microcontroller processes the sensor data and automatically regulates the purification mechanism without human intervention. Real-time monitoring is achieved using a cloud platform, enabling users to visualize air quality data and receive alerts through a mobile application. The proposed system offers a cost-effective, energy-efficient, and intelligent solution for maintaining healthy indoor environments.